Social vulnerability in the pandemic period: correlation between social determinants of health and COVID-19 incidence in Brazilian regions (Research, Society and Development, 2020)
The social determinants of health directly influence in the health-disease process. In the pandemic caused by the novel Coronavirus, denominated Coronavirus Disease 2019 (COVID-19), these factors imply the transmission and worsening of the disease. This work is aimed to correlate the social vulnerability in Brazilian regions with the number of COVID-19 confirmed cases. The analysis was made through a qualitative approach in the search for information made available by public agencies such as the Brazilian Institute of Geography and Statistics (IBGE), State Department of Health, Municipal Department of Health and the literature indexed on the Scientific Electronic Library Online (SciELO) database using the health descriptors: “Social determinants of health”, “Health-disease process”, “Social vulnerability” and “COVID-19”. As results, the discrepancy between regionals incidence and mortality rates suggests a relationship with social inequality and COVID-19 indices in the regions of Brazil. North and Northeast had the worst rates in most of the evaluated parameters. Therefore, the vulnerable population of fundamental resources for dignified survival is more susceptible to aggravations and failures in coping with new infectious diseases.